Analisis Proses Penentuan Kelayakan dan Pengamanan Penggunaan Overhead Crane Menggunakan Metode Pemeriksaan dan Pengujian Teknis K3 - Annisa Fyona; Miduk Parulian Nababan; Budi Baharudin; Rahman Hakim (Politeknik Negeri Batam, 2022)
In the world of industry, you can find many tools or machines that are used to simplify the process of human work. One type of tool that is widely used is a lifting equipment. Lifting equipment are equipment that are made and installed to lift, down, set and hold workpieces or load. One example of a lifting equipment is an overhead crane. Most overhead cranes are installed on the roof of the building (indoors) but can also be used outdoors. Along with the time to use an overhead crane, the longer it will definitely experience a decrease in quality both in terms of components and functions, it is necessary to control the feasibility management system and use permit. Based on the regulations of the Ministry of Manpower is Permenaker no. 8 tahun 2020 about K3 of lifting equipment and transport equipment. Which each lifting and transport equipment’s before being operated should be inspected and tested in advance, as well as periodic testing is carried out in accordance with the test standards have determined. The final task research uses descriptive qualitative analysis method, which is to get data by direct observation on the tool. When inspection and testing has been carried out according to standards, the overhead crane will receive a certificate and a safe use permit.